Temperature-induced transport changes in molecular junctions based on a spin crossover complex. Issue 18 (16th April 2019) - Poggini, Lorenzo; Gonidec, Mathieu; Canjeevaram Balasubramanyam, Ram Kumar; Squillantini, Lorenzo; Pecastaings, Gilles; Caneschi, Andrea; Rosa, Patrick
Abstract : This work describes the study of molecular junctions embedding the spin crossover complex [Fe(H2 B(pz)2 )2 (phen)] as an active switchable thin film. Abstract : This work describes the study of molecular junctions embedding the spin crossover complex [Fe(H2 B(pz)2 )2 (phen)] as an active switchable thin film. In these junctions we observed that the spin state conversion causes a gradual increase in the current density, which may be due to a crossover from direct tunneling to multi-step hopping.